Stakeholder perspectives on the effectiveness of the Ifakara-Lupiro-Mang’ula wildlife management area in Southern Tanzania - Lucia J. Tarimo; Deogratius R. Kavishe; Fidelma Butler; Gerry F. Killeen; Felister Mombo (Environmental Challenges, 2025)
In Tanzania, Wildlife Management Areas (WMAs) are established on village lands and managed in a devolved manner by local community stakeholders. WMAs are intended to conserve wildlife outside core protected areas, like parks and reserves, while also enabling local communities to derive tangible benefits from wildlife and other natural resources. Here the perceptions of various stakeholders regarding the effectiveness of the Ifakara-Lupiro-Mang’ula (ILUMA) WMA in southern Tanzania were assessed, in terms of its conservation, livelihood and community development functions. Thematic analysis of national, regional, district and village-level stakeholder perspectives, surveyed through in-depth interviews, focus group discussions and a public stakeholders meeting, indicated the WMA had succeeded to only a very modest extent. All participants narrated extensive encroachment by livestock grazing, agriculture, illegal fishing, meat poaching, deforestation, charcoal burning, timber harvesting and even permanent settlements. Contributing factors include a recently growing influx of agro-pastoralist immigrants, top-down political interference, financial constraints, financial mismanagement, limited resources for operations, lack of conservation education, investors or government support, and displaced encroachment pressure from a park and a reserve nearby that had both been recently upgraded. To ensure future success and sustainability of the WMA, participants recommended enhancing stakeholder involvement and community participation in WMA management, improved operational collaboration with the nearby park and reserve, WMA constitution overhaul to adopt current best practices, building local stakeholder capacity and conservation education for local communities. The WMA should explore additional livelihood and income-generating options beyond tourism, for example sustainable fishing or forestry-based carbon finance. It should also resolve ongoing land use conflict between long-established stakeholder villages and more recently arrived agro-pastoralists.